Performance of sesame variety YLM-66 (SARADA) under Cluster Frontline Demonstrations in Andhra Pradesh: Performance of sesame variety YLM-66 (SARADA) under Cluster Frontline Demonstrations in Andhra Pradesh - MALATHI B; A BHASKARAN; JV PRASAD; YG PRASAD; A R REDDY; C CHAITHANYA; B VANUSHA; NSR JOGAMBA (Journal of Oilseeds Research, 2023)
A total of 1530 Cluster frontline demonstrations were conducted in farmers’ fields with sesame variety YLM-66. The demonstration yields with YLM-66 and recommended package of practices ranged between 7.37 q ha-1 to 8.13q ha-1 with average yield of 7.71 q ha-1 which was 30.08% higher than the farmer’s practice (5.93 q ha-1). The average net returns of 39201 Rs. ha-1 and benefit cost ratio of 2.81 were recorded with improved technology against net returns of 26573 Rs. ha-1 and benefit cost ratio of 2.34 in farmers’ practice.